Islamic Education Management in the Context of the Industrial Revolution 4.0 and Society 5.0 at IAIN Curup - Permanasari, Revi; Warsah , Idi; Warlizasus , Jumira; Apriani , Eka (Corolla International Conference, 2025)
This study aims to analyze Islamic education management within the context of the Industrial Revolution 4.0 and Society 5.0 at the State Islamic Institute of Curup (IAIN Curup). The global phenomenon of the Industrial Revolution 4.0, characterized by digitalization, artificial intelligence, and the Internet of Things (IoT), has significantly transformed educational management systems. Society 5.0 emphasizes the balance between technological advancement and human-centered values, aligning with Islamic management principles grounded in tauhid, ukhuwah, and maslahah. This research employed a sequential exploratory mixed-method approach, involving 50 survey respondents and 10 interview informants comprising leaders, lecturers, staff, and students. Quantitative data were analyzed using descriptive statistics (SPSS), while qualitative data were analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that Islamic education management principles remain highly relevant in the digital era by integrating spiritual values with technological efficiency. IAIN Curup has implemented digital transformation through an integrated academic information system, e-learning, and Islamic value-based governance. Key supporting factors include visionary leadership, institutional policy support, and human resource readiness, while constraints involve limited infrastructure and digital competence gaps. The study proposes a conceptual model called the Tawhidic Adaptive Management Model (TAMM), which integrates tauhid, Islamic digital leadership, ethical innovation, and maslahah-oriented collaboration.